Malay reserve land: how to turn a basketful of problems into a bouquet of opportunities / Nurdeenie Abdul Rashid and Samira Khalili - Abdul Rashid, Nurdeenie; Khalili, Samira (2008)
Too many people have commented on the policy of Malay Reserve Land. You have a group of people that holds it a sentiment to heart and then you have the group averse to the whole idea of the policy. What is undoubtedly agreed by all parties however, is that attached to a Malay Reserve Land is an abundance of problems; a basketful of problems. Therefore, this paper is aimed to look in to the ways in which this basketful of problems can be turned into a bouquet of opportunities. Therefore, this paper is aimed to look in to the ways in which this basketful of problems can be turned into a bouquet of opportunities. The focal purpose of this paper is to determine the problems underlying Malay Reserve Lands and to offer recommendations on how to resolve it. Firstly, the fact that the lands are of a lower value than other normal lands will be looked at and the reasons as to why it is so. The policy of Malay Reserve Land under land acquisition by the government will also be looked at. Besides that, a comparison will also be made between the Malay Reservation Enactment 1933 (Cap. 142) that involves the former Federated Malay States with the five other State Enactments involving the former Unfederated Malay States, and in doing so, proving the need of uniformity and cohesiveness of laws regarding Malay Reserve Land. The study will also dissect each scheme of prohibition in all the significant laws.